2005
DOI: 10.1152/jn.00228.2005
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Contralateral SI Activity Reveals Hindlimb Receptive Fields in the SI Forelimb-Stump Representation of Neonatally Amputated Rats

Abstract: Pluto, Charles P., Nicolas L. Chiaia, Robert W. Rhoades, and Richard D. Lane. Reducing contralateral SI activity reveals hindlimb receptive fields in the SI forelimb-stump representation of neonatally amputated rats. J Neurophysiol 94: 1727-1732, 2005. First Published March 30, 2005 doi:10.1152/jn.00228.2005. In adult rats that sustained forelimb amputation on the day of birth, Ͼ30% of multiunit recording sites in the forelimb-stump representation of primary somatosensory cortex (SI) also respond to cutaneous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 50 publications
4
25
1
Order By: Relevance
“…Ipsilateral sensory inputs may normally reduce contralaterally driven activity in the cortex and sharpen response properties by reducing surround receptive fields of cortical neurons (Shuler et al, 2001;Pluto et al, 2005;Schmidt et al, 2006). Our data indicate that the cumulative effect of reduced ipsilateral sensory activity is an increase in stimulus-driven activity in the sensoryspared hemisphere.…”
Section: Ipsilateral Sensory Input and Spared Whisker Plasticitymentioning
confidence: 67%
See 2 more Smart Citations
“…Ipsilateral sensory inputs may normally reduce contralaterally driven activity in the cortex and sharpen response properties by reducing surround receptive fields of cortical neurons (Shuler et al, 2001;Pluto et al, 2005;Schmidt et al, 2006). Our data indicate that the cumulative effect of reduced ipsilateral sensory activity is an increase in stimulus-driven activity in the sensoryspared hemisphere.…”
Section: Ipsilateral Sensory Input and Spared Whisker Plasticitymentioning
confidence: 67%
“…Although transection of the corpus callosum, the main anatomical structure that connects the two cortical hemispheres, results in only subtle sensory and motor deficits (Gazzaniga, 2000), many studies have confirmed that cortical neuron responses can be strongly influenced by activation of peripheral ipsilateral inputs (Armstrong-James and George, 1988;Clarey et al, 1996;Shuler et al, 2001Shuler et al, , 2002Pluto et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…DGZ also projects directly to S1 barrel cortex (Chapin et al, 1987;Koralek et al, 1990). Moreover, since horizontal connections in cortex including somatosensory cortex have been shown to recruit inhibitory networks under some conditions (Tucker and Katz, 2003;Pluto et al, 2005;Keniston et al, 2010), it is possible that the projections from the DGZ to barrel cortex terminate on inhibitory FSUs that could cause subthreshold changes leading to an increased excitability in inhibitory neurons. Thus, this model predicts that the click component of the CS stimulus would activate the DGZ, which could increase the excitability of the FSUs in barrel cortex via corticocortical connections leading to a suppression of firing in the longer latency component of the barrel field responses.…”
Section: Discussionmentioning
confidence: 99%
“…Schnitzler et al (1995), using magnetoencephalography (MEG), reported that concurrent tactile stimulation of the ipsilateral hand enhances the response of SI to stimulation of the contralateral median nerve. Conversely, (1) Korvenoja et al (1995) reported that the SI activation (detected using MEG) evoked by contralateral median nerve stimulation is suppressed during ipsilateral hand movement, (2) functional magnetic resonance imaging studies in both monkeys (Lipton et al, 2006) and humans (Hlushchuk et al, 2006) showed that an ipsilateral skin stimulus evokes CNS actions that partially suppress the SI response to a contralateral stimulus, (3) destruction of SI in one hemisphere (rats) was shown to be accompanied by the appearance (in the opposite SI) of neurons with bilateral receptive fields [interpreted to indicate that SI activity exerts a suppressive influence on SI neurons in the opposite hemisphere (Pluto et al, 2005)], and (4) low-frequency transcranial magnetic stimulation of sensorimotor cortex (in humans, Pal et al, 2005) was found to reduce excitability in the opposite hemisphere. Viewed collectively, these findings raise the possibility that the response of the SI hand region to a tactile stimulus (and thus the stimulus-evoked perceptual experience) may be subject to modulatory influences arising from the ipsilateral hand.…”
Section: Introductionmentioning
confidence: 99%